A Multicenter Single-Arm Objective Performance Criteria Trial to Determine the Efficacy and Safety of High-Frequency Irreversible Electroporation as Primary Treatment for Localized Prostate Cancer: A Study Protocol - He, Bi-Ming; Xue, Wei; Yan, Wei-Gang; Yin, Lei; Dong, Bai-Jun; Zhou, Zhi-En; Lin, Heng-Zhi; Zhou, Yi; Wang, Yan-Qing; Shi, Zhen-Kai; Zhou, Hai; Wang, Shuai-Dong; et al. (Frontiers in Oncology, 2021)
Introduction The classical pathway for the therapy of low- to intermediate-risk localized prostate cancer is radical prostatectomy or radiation therapy, which has shown a high incidence of complications, including erectile dysfunction, urinary incontinence, and bowel injury. An alternative pathway is to perform an ablation by some energy to the localized lesion, known as focal therapy. High-frequency irreversible electroporation (H-FIRE) is nonthermal energy that can be used in cancer ablation to deliver pulsed high-voltage but low-energy electric current to the cell membrane and to invoke cell death. An H-FIRE pathway has been reported to be tissue-selective, which leads to fewer side effects. Methods and Analysis This is a multicenter and single-arm objective performance criteria (OPC) study, in which all men with localized prostate cancer are allocated to H-FIRE ablation. This trial will assess the efficacy and safety of the H-FIRE ablation for prostate cancer. Efficacy will be assessed by prostate biopsy 6 months after treatment while safety will be assessed by adverse event reports and questionnaires. The main inclusion criteria are moderate to low-risk prostate cancer in NCCN risk classification and had no previous therapy for prostate cancer. A sample size of 110 participants is required. The primary objective is to determine whether the detection rate of clinically significant cancer by prostate biopsy is less than 20% after the H-FIRE ablation. Ethics and Dissemination This study has obtained ethical approval by the ethics committee of all participating centers. The results of the study will be submitted for dissemination and publication in peer-reviewed journals. Conclusions This multicenter single-arm objective performance criteria trial will evaluate the efficacy and safety of the use of high-frequency irreversible electroporation in treating prostate cancer. Strengths and Limitations of This Study A comprehensive evaluation of imaging and histopathology is used to determine the effect of treatment. Questionnaires were used to assess the treatment side effects. Multicenter and pragmatic designs capacitate higher generalizability. A limitation of this trial is that the prostate biopsy as an endpoint may not be as accurate as of the specimen from prostate prostatectomy. Another limitation is the 6-month follow-up time, making this trial challenging to come to firm conclusions regarding the efficacy and safety of IRE in the long term. Clinical Trial Registration ClinicalTrials.gov, NCT03838432